2020
DOI: 10.1111/cea.13553
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of severe wheeze exacerbations from infancy to school age and their association with early‐life risk factors and late asthma outcomes

Abstract: Introduction Exacerbation‐prone asthma subtype has been reported in studies using data‐driven methodologies. However, patterns of severe exacerbations have not been studied. Objective To investigate longitudinal trajectories of severe wheeze exacerbations from infancy to school age. Methods We applied longitudinal k‐means clustering to derive exacerbation trajectories among 887 participants from a population‐based birth cohort with severe wheeze exacerbations confirmed in healthcare records. We examined early‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 48 publications
1
33
0
3
Order By: Relevance
“…In this issue of the Journal, Deliu et al look at the longitudinal trajectories of medical record confirmed severe exacerbations of wheeze from infancy into childhood. 1 They used a data-driven methodology to derive exacerbation trajectories in the Manchester Asthma and Allergy Study cohort. 2 Amongst the 160 participants with at least one severe exacerbation, they found two clusters: "Infrequent exacerbations" (93.7%) and "Early-onset frequent exacerbations" (6.3%) ( Figure 1).…”
Section: Severe Wheeze Aspergillus and A New Approach For Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal, Deliu et al look at the longitudinal trajectories of medical record confirmed severe exacerbations of wheeze from infancy into childhood. 1 They used a data-driven methodology to derive exacerbation trajectories in the Manchester Asthma and Allergy Study cohort. 2 Amongst the 160 participants with at least one severe exacerbation, they found two clusters: "Infrequent exacerbations" (93.7%) and "Early-onset frequent exacerbations" (6.3%) ( Figure 1).…”
Section: Severe Wheeze Aspergillus and A New Approach For Anaphylaxismentioning
confidence: 99%
“…In this issue of the Journal, Deliu et al look at the longitudinal trajectories of medical record confirmed severe exacerbations of wheeze from infancy into childhood . They used a data‐driven methodology to derive exacerbation trajectories in the Manchester Asthma and Allergy Study cohort .…”
mentioning
confidence: 99%
“…as well as to previously machine learning-derived allergy clusters [290][291][292][293] , to assess involvement in allergy development. Subsequently, possible predictive and longitudinal effects on allergy outcomes of the circulating chemokine levels were investigated using logistic regression and generalised estimating equation (GEE) models.…”
Section: Paper I -Chemokine Studies In the Manchester Asthma And Allementioning
confidence: 99%
“…Furthermore, we ascertained the relationship between these chemokines and previously described clusters of allergic diseases derived using machine learning in this cohort. [41][42][43][44] Materials And Methods…”
Section: Introductionmentioning
confidence: 99%